Educación física inclusiva en Brasil: entrevista con Marli Nabeiro - Mele, Ayelen Magali (2013)
Dr. Marli Nabeiro addresses, in this interview, topics related to inclusive education in Brazil, specifically focusing on the approach conducted from Physical Education. She makes a review of the treatment given to disabled people throughout history and how the concept towards these people has evolved. Dr. Nabeiro also addresses the influence of these changes in education and how professionals are currently working in an inclusive way. In relation to this, she recounts the work being carried out from Physical Education to improve practices in schools and describes one of the strategies used for inclusion based on the training of a peer acting as a tutor.